Clinical Reference Values for Dynamic Plantar Pressure Assessment in Healthy Young Adults: Sex Differences and Bilateral Symmetry - Daniela Matei; Elena Taina Avramescu; Ana Maria Bumbea; Simona Pătru; Dănuț Visarion Caimac; Anca Maria Amzolini; Carmen Daniela Neagoe; Gheorghe Ionescu; Klejda Tani; Miruna Andreiana Matei; Sergiu Cazacu; Diana Clenciu; et al. (Life, 2026)
This study aimed to establish a sex- and side-specific, platform- and population-specific descriptive reference dataset for dynamic plantar loading in healthy young adults and to investigate regional variability, mean left–right differences, and differences between female and male participants. Methods: A cross-sectional observational study included 90 healthy young adults selected from 102 initially recruited participants after predefined quality-control procedures. Bilateral plantar loading recordings were obtained using the RSscan platform under standardized conditions. Maximum force, impulse, and contact area were analyzed as the primary reference parameters across ten anatomical plantar regions, while load rate was additionally evaluated in the variability analysis. Sex- and side-specific descriptive statistics were calculated, and inter-individual variability was assessed using the coefficient of variation. Mean left–right differences were evaluated using paired Student’s t-tests. Differences between female and male participants were evaluated separately for each side using Welch’s independent-samples t-tests, with Benjamini–Hochberg false discovery rate correction for multiple comparisons. Results: Sex- and side-specific descriptive reference values were obtained for maximum force, impulse, and contact area. Maximum force and impulse were highest in the heel and central metatarsal regions, whereas contact area was greatest in the midfoot and heel. Contact area showed comparatively low inter-individual variability across plantar regions, whereas maximum force exhibited greater regional variability, particularly in the forefoot. Significant differences between female and male participants were observed for several parameters and plantar regions after correction for multiple comparisons. No statistically significant mean side differences were detected between corresponding plantar loading parameters of the left and right feet (all p > 0.05); this finding should not be interpreted as evidence of individual bilateral symmetry or equivalence. Conclusions: The present study provides a platform- and population-specific descriptive reference dataset for plantar loading in healthy young adults assessed using the RSscan system under standardized acquisition conditions. The reported values may serve as descriptive benchmarks for assessments performed using comparable measurement conditions; however, they should not be interpreted as diagnostic thresholds. Further validation in larger and more diverse populations and across different plantar pressure measurement systems is required before broader clinical application.